Evaluation of the treatment efficacy of patients with multiple sclerosis using Barthel index and Expanded Disability Status Scale (Journal of Health Sciences, 2014)
Introduction: Multiple sclerosis (MS) is a chronic, autoimmune and progressive multifocal demyelinating disease of the central nervous system. The aim of this study was to evaluate rehabilitation of patients with multiple sclerosis using BI (Barthel index) and EDDS (Expanded Disability Status Scale).Methods: A clinical observational study was made at the clinic for physical medicine and rehabilitation in Sarajevo. We analyzed 49 patients with MS in relation of gender, age and level of disability at admission and discharge, patient disability were estimated using EDDS scale. The ability of patients in their activities of daily living were also analyzed according to the BI at admission and discharge.Results: Of the total number of patients (n=49) there were 15 men and 34 women. The average age of female patient was 42.38±13.48 and male patient 46.06±9.56. EDDS values were significantly different at the beginning and at the end of the therapy (p=0.001) as was the value of BI (p=0.001).Conclusion: MS patients, after the rehabilitation in hospital conditions show significant recovery and a reduced level of disability; they show higher independence in activities but rehabilitation demands individual approach and adjustment with what patients are currently capable of achieving.